Model Permainan Outbound untuk Meningkatkan Kerjasama Anak Berkebutuhan Khusus - Agung Yudha Catur Rizal; Herman Tarigan; Ade Jubaedi (JUPE (Jurnal Penjaskesrek), 2017)
This study aims to This study aims to determine the effectiveness of teamwork on the increase of students with high-class special needs in Elementary Schools Extraordinary Elementary School of Lampung Province. The type of research used is comparative experiment. With a population of 30 high school students, consisting of 13 deaf students, 10 mice and 7 speech masters.Techniques of data collection using outbound research instrument, covering discipline, responsibility, cooperation, tolerance, attitude. After the initial test students are given outbound training in accordance with the training program that has been made then performed the final test. Preliminary test data and final tests were analyzed using t-test data analysis techniques and calculated the effectiveness test. The results show that the outbound game model is effective in improving studentworkwork. And it can be concluded that the Bakiak game model is more effective in improving teamwork of high-class students in the extraordinary Elementary School of PKK Lampung Province.Penelitian ini bertujuan untuk mengetahui efektivitas teamwork terhadap peningkatan siswa anak berkebutuhan khusus kelas tinggi di SD Luar Biasa PKK Provinsi Lampung. Jenis penelitian yang digunakan adalah eksperimen komparatif. Dengan populasi sebanyak 30 siswa kelas tinggi, yang terdiri dari 13 siswa tuna rungu, 10 tuna grahita, dan 7 tuna wicara. Teknik pengumpulan data menggunakan instrument penelitian outbound, meliputi aspek displin, tanggung jawab, kerjasama, toleransi, sikap. Setelah tes awal siswa diberikan pelatihan outbond sesuai dengan program latihan yang telah dibuat kemudian dilakukan tes akhir. Data tes awal dan tes akhir dianalisis menggunakan teknik analisis data uji-t dan di hitung tes uji efektivitasnya. Hasil penelitian menunjukkan bahwa model permainan outbound efektif dalam meningkatkan teamwork siswa. Serta dapat disimpulkan bahwa model permainan Bakiak lebih efektif dalam meningkatkan teamwork siswa kelas tinggi di SD Luar Biasa PKK Provinsi Lampung.Kata Kunci: outbond, permainan, kerjasama.